Gender in water and sanitation provision and responses to the COVID-19 pandemic in rural Ghana - Mapedza, Everisto D.; Adewale, D.; Seyram, R.; Asare, G.; Cofie, Olufunke O.; Nikiema, J.; Gebrezgabher, Solomie A.; Njenga, M.; Mendum, R. (International Water Management Institute, 2025)
The study "Gender in Water and Sanitation Provision and Responses to the Covid-19 Pandemic in Rural Ghana" delivers a compelling analysis of the critical intersection between gender, water access, sanitation, and the far-reaching impacts of the Covid-19 pandemic in the Ga South District of Greater Accra, Ghana. It underscores the urgent need to address gender disparities, revealing how the pandemic exacerbated existing inequalities in water and sanitation services. Through a robust collection of data from questionnaires, focus group discussions, and key informant interviews, the research illuminates the distinct experiences of women and men within the context of water access and hygiene. The findings highlight the pandemic's differential effects, including a surge in domestic violence and an alarming rise in teenage pregnancies, underscoring the vulnerability of certain demographic groups. This study calls for immediate and targeted interventions to transform water and sanitation services, emphasizing gender-sensitive strategies that can effectively address the unique challenges faced by diverse communities. By aligning with Sustainable Development Goal (SDG) indicators on water stress and availability, this working paper provides actionable insights for policymakers, advocating for comprehensive approaches that prioritize equity and resilience in rural settings. This research serves as a vital catalyst for change and a deeper understanding of the interplay between gender and water management in crisis contexts such as that induced by Covid-19.